Modelling and Optimization of the Compressive Strength of High Volume Fly Ash ECC with Low Modulus PVA Fiber Using Response Surface Methodology (RSM) - Isyaka Abdulkadir; Bashar S. Mohammed (Journal of Infrastructure & Facility Asset Management, 2021)
Engineered cementitious composite (ECC) also known as bendable concrete is popular for its high ductility behavior under tensile load. However, to achieve this amazing characteristic, the compressive strength is usually compromised due to the high volume fly ash (HVFA) effect of reducing the composite’s toughness. This research is aimed at developing a response surface model and optimization of the two major ingredients (fly ash and PVA fiber) with the view to developing a composite with the desirable compressive strength for structural application. Results indicated that although the FA affects the compressive strength development negatively, the presence of PVA fiber especially at 1 to 1.5% volume fraction enhances the compressive strength. A quadratic response surface model was developed and was analyzed using analysis of variance (ANOVA) and found to have a R2 value of 96.82%. The model validation showed a very good agreement between the predicted and the experimental results with less tha 5% error margin.